Bystanders in workplace bullying: working university students' perspectives on action versus inaction. (8th February 2019) - Paull, Megan; Omari, Maryam; D'Cruz, Premilla; Güneri Çangarli, Burcu
Abstract : There is increasing interest in bystanders to workplace bullying, including from human resource management (HRM) perspectives. This paper draws on literature from the fields of sexual harassment and helping behaviour to develop understanding of bystander action and inaction. Part of a project on workplace bullying, this study used online story‐based responses from university students in Australia, India and Turkey with workplace experience to elicit bystander and target interpretations of the behaviour. Findings suggest that even when bystanders are aware of bullying, they do not always intervene for reasons ranging from powerlessness and fear to avoidance and ignorance. Helping behaviours, including private support or making a report, were described by some respondents, with contextual factors linked to the perpetrator or the organisation influencing responses. The importance of the HRM role in facilitating bystander action, drawing on the helping behaviour and sexual harassment literature, is a focus of the findings and implications. Abstract : Key points Action/inaction of bystanders to workplace bullying is a product of a range of factors including context. To better understand bystander responses, theories relating to helping behaviour and sexual harassment provide guidance. Imbuing feelings of responsibility and empowerment are strategies to encourage bystander action. Organisational climate, culture and context, especially trust, can help promote positive action from bystanders. Human resource practitioners have a key role in creating environments where bystanders help ameliorate workplace bullying.